Effect of Blood Contamination on Marginal Adaptation and Surface Microstructure of Mineral Trioxide Aggregate: A SEM Study - Amin Salem Milani; Saeed Rahimi; Mohammad Froughreyhani; Mahdi Vahid Pakdel (Tabriz University of Medical Sciences, 2013)
Background and aims. In various clinical situations, mineral trioxide aggregate (MTA) may come into direct contact or even be mixed with blood. The aim of the present study was to evaluate the effect of exposure to blood on marginal adaptation and surface microstructure of MTA. Materials and methods. Thirty extracted human single-rooted teeth were used. Standard root canal treatment was carried out. Root-ends were resected, and retrocavities were prepared. The teeth were randomly divided into two groups (n = 15): in group 1, the internal surface of the cavities was coated with fresh blood. Then, the cavities were filled with MTA. The roots were immersed in molds containing fresh blood. In group 2, the aforementioned procedures were performed except that synthetic tissue fluid (STF) was used instead of blood. To assess the marginal adaptation, "gap perimeter" and "maximum gap width" were measured under scanning electron microscope. The surface microstructure was also examined. Independent samples t-test and Mann-Whitney U test were used to analyze the data. Results. Maximum gap width and gap perimeter in the blood-exposed group were significantly larger than those in the STF-exposed group (p < 0.01). In the blood-exposed group, the crystals tended to be more rounded and less angular compared with the STF-exposed group, and there was a general lack of needle-like crystals. Conclusion. Exposure to blood during setting has a negative effect on marginal adaptation of MTA, and blood-exposed MTA has a different surface microstructure compared to STF-exposed MTA.